Effect of different grid shapes in wireless mesh network-genetic algorithm system. (1st January 2014) - Oda, Tetsuya; Sakamoto, Shinji; Barolli, Admir; Spaho, Evjola; Barolli, Leonard; Xhafa, Fatos
Grid computing have emerged as scientific and technical work, where geographically distributed computers, are used to create virtual supercomputers of vast amount of computing capacity able to solve complex problems in less time than before. Thus, within the last years we have witnessed how grid computing has helped to achieve breakthroughs in meteorology, physics and other computing-intensive fields. Wireless Mesh Networks (WMNs) are particularly suited for providing the communications required for a robust, self-healing grid architecture. The good performance and operability of WMNs depend on placement of mesh routers nodes in the geographical deployment area. In this paper, we consider the grid topology and evaluate the performance of WMN-GA system for node placement problem in WMNs. We consider different distributions of mesh clients and different grid shapes. The simulation results show the effect of grid shapes in the performance of WMN-GA. The system performs better for normal distribution.